ChemInform Abstract: Hydrogen‐Borrowing and Interrupted‐Hydrogen‐Borrowing Reactions of Ketones and Methanol Catalyzed by Iridium. Issue 24 (June 2015) - Shen, Di; Poole, Darren L.; Shotton, Camilla C.; Kornahrens, Anne F.; Healy, Mark P.; Donohoe, Timothy J.
Abstract: [IrCl(cod)]2 as the catalyst promotes hydrogen‐borrowing reaction of ketone enolates with methanol to give enones (III) which can react with excess methanol as nucleophile to yield mixtures of methoxymethyl derivatives (IV) and the enones (III).